Programas de recuperação fiscal – refis de uma análise sob a ótica da teoria dos jogos - Araújo, Francisco Ângelo de (2009)
The present work focuses on the analysis of fiscal recovery programs - REFIS - beneath the optics of Game Theory. The theory of public choices and the game theory form the core of the theoretical framework of this present work. An analysis of the dynamics of the outstanding active debt of the Union and the State of Ceará is undertaken with the aim of showing that there is a problem which requires a government decision. Is looked for through the Cournot Model, clarify that firms when decide to collect the tribute or not, have their quantities and profits changed for bigger. Finally, is formalized an model in that analyzes the decisions of government - of edit or not edit the REFIS, and the decisions of the taxpayer - of retract or not retract the tax. The outcome of game shows that for the government, the best strategy is to not edit the REFIS. The results show even that for the taxpayer, the best strategy is to retract the tribute on time, in case in the government does not edit the REFIS, however is more advantageous for him retract with the benefit the case where there is the edition of the program.